1990
DOI: 10.1080/01688639008400978
|View full text |Cite
|
Sign up to set email alerts
|

Procedural memory in Parkinson's disease: Impaired motor but not visuoperceptual learning

Abstract: A current model proposes that memory consists of two functionally separate systems that have different neurological substrates. Declarative memory appears to be dependent on the diencephalic medial temporal lobe system whereas some speculate that the basal ganglia may be a neurological substrate for procedural memory. This study tested the role of the basal ganglia in regulating different types of procedural skills by comparing performance on a motor and a visuoperceptual skill learning task. Twenty Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
2
18

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(155 citation statements)
references
References 39 publications
6
129
2
18
Order By: Relevance
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with basal ganglia damage are sometimes spared on non-declarative learning tasks (Bondi & Kaszniak, 1991;Harrington et al, 1990;Heindel et al, 1989;Reber & Squire, 1999;Smith, 2001;Witt et al, 2002), and are sometimes impaired on declarative memory tasks (Bondi & Kaszniak, 1991;Breen, 1993;Owen et al, 1993a;Pillon et al, 1996;Whittington et al, 2000). Indeed, fMRI often reveals both MTL and basal ganglia activation during both declarative and non-declarative tasks (Aizenstein et al, 2004;Degonda et al, 2005;Poldrack et al, 2001;Rose et al, 2002;Schendan et al, 2003).…”
Section: Memory Systems and The Basal Ganglia: Limitations And Open Qmentioning
confidence: 99%
“…Subjects with basal ganglia disorders such as Huntington's disease (Knopman and Nissen 1991;Willingham and Koroshetz 1993), Parkinson's disease (Ferraro et al 1993;Pascual-Leone et al 1993;Jackson et al 1995;Westwater et al 1998;Sommer et al 1999;Stefanova et al 2000) or pharmacologic treatments that affect the basal ganglia (Knopman 1991) demonstrate greatly reduced, or entirely absent, interference effects, indicating compromised implicit learning. These SRT deficits in subjects with basal ganglia dysfunction are not simply due to motor performance dysfunction (Harrington et al 1990), as subjects with damage restricted to the basal ganglia as a consequence of infarct or hemorrhage are significantly impaired in both a motor and nonmotor version of the SRT (Vakil et al 2000). Furthermore, Vakil et al (2000) found that while the basal-ganglia infarct subjects were significantly impaired in the SRT in comparison with intact-control subjects, the two groups did not differ on several tests of declarative (explicit) memory function.…”
mentioning
confidence: 99%